Influence of Online Reviews on Consumer Purchase Decisions: Evidence from the Kathmandu Valley - Sharma, Anita; Kumar Basyal, Devid; Lawaju, Purnima; Thakur, Abhishek; Raj Paudel, Udaya (Nepalese Journal of Insurance and Social Security, 2024)
Purpose: The main objective of conducting this research is to analyze the impact of online reviews on consumer purchase intention in Kathmandu Valley. Study is considered about how consumers change their purchase intention with the help of online reviews.Design/methodology/approach: In this study, explanatory research is adopted to understand the relationship between each variable. The study employs the Stimulus-Organism-Response theory, and 403 data has been collected by the setup of the questionnaire and data was collected in KOBO Toolbox. Data was analyzed using descriptive and inferential analysis.Findings: The study shows that social presence and perceived information quality both positively impact consumer satisfaction and trust. Trust significantly influences satisfaction and purchase intention. However, social presence and information quality do not directly affect purchase intention.Conclusion: To improve online review credibility, policymakers should enforce regulations against fraudulent reviews, support IT advancements for better review management, and educate consumers about online review pitfalls. These measures will enhance the reliability of review platforms and aid consumer decision-making.Implication: The study highlights the importance of trust and satisfaction in driving purchase intentions, emphasizing the need for businesses to manage online reviews professionally, and for policymakers to enforce regulations against fraudulent reviewsJEL Classification: L86, M31, C12, L84